Close relationships between neck and upper-back stiffness and transverse cervical artery flow velocity - Shibasaki, Shohei; Kishino, Tomonori; Sei, Yoriko; Harashima, Keiichiro; Sakata, Konomi; Ohnishi, Hiroaki; Watanabe, Takashi (European journal of applied physiology, 2024)
Purpose Neck and upper-back stiffness is encountered in daily life, with symptoms appearing as dullness or aches predominantly in the trapezius muscle (TM). Our previous study demonstrated that TM hardness as measured with a muscle hardness meter correlates well with transverse cervical artery (TCA) flow supplying the TM. Muscle hardness meters, however, cannot measure hardness in the TM alone. Meanwhile, recent advances in ultrasound elastography have enabled the evaluation of localized hardness in targeted tissues. The present study, therefore, aimed to clarify the relationship between TM hardness as measured by elastography and TCA hemodynamics as measured on Doppler sonography, with reference to daily symptoms of upper-back stiffness. Methods The study population comprised 66 healthy young adults (32 males, 34 females; mean age, 21 ± 1 years). Relationships were evaluated between TM hardness as a negative correlate of strain ratio from elastography and TCA hemodynamics on Doppler sonography. Hemodynamics in the TCA were evaluated according to the frequency of neck and upper-back stiffness. Results TM strain ratio correlated with peak systolic velocity (PSV) in the TCA ( r = 0.273, p = 0.036), particularly in symptomatic subjects ( r = 0.417, p = 0.022). PSV in the TCA decreased with increasing frequency of daily symptoms ( p = 0.045). Conclusion TCA hemodynamics correlated with muscle hardness when evaluating localized TM hardness. This relationship and low PSV in the TCA were evident in symptomatic subjects. These results suggest that PSV in the TCA is associated with neck and upper-back stiffness.